PENGARUH MODEL PEMBELAJARAN BERBASIS PROYEK TERHADAP KETERAMPILAN KOLABORATIF PESERTA DIDIK KELAS V DI SDN 166 PALEMBANG - Tri Juniarti, Mawar; Boty, Middya; Tasya Jadidah, Ines (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to determine the effect of Project Based Learning (PjBL) on students' collaborative skills in grade V at SDN 166 Palembang. This research employed a quantitative approach with a quasi-experimental method using a nonequivalent control group design. The sample consisted of 54 students divided into experimental and control classes. Data were collected using observation sheets based on collaborative skill indicators, including active contribution, cooperation, responsibility, productivity, and mutual respect. The results showed that the experimental class experienced a higher improvement than the control class. The average posttest score of the experimental class was 80, while the control class was 73,14. The Independent Sample t-test showed a significance value of 0.000 < 0.05, indicating a significant effect of PjBL on students’ collaborative skills. Therefore, Project Based Learning is effective in improving collaborative skills in elementary school students.